High gain buck-boost matrix converter - Chauhan A.K.; Reza M.M.; Raghuram M.; Singh S.K. (My University, 2025)
Boosting factor of power converter is a critical requirement for high voltage low power applications. There are many extended DC-DC converter topologies available for boosting output voltage beyond the traditional boost converters. However, for direct AC-AC conversion boosting factor of four can be achieved using single inductive element or impedance source network. Though higher boosting beyond this factor is achievable, extra switches are needed. This paper proposes a new approach of direct AC-AC conversion for higher boosting of output voltage, without adding extra switches to a recently proposed AC-AC converter. This was made possible by restricting positive inductor current both during positive and negative AC half cycles. Instead of single inductive element, switched inductive network is added to the AC-AC converter. Moreover, as this concept is implemented using six switch matrix converter, the commutation problem of a typical AC-AC converter is avoided. © 2016 IEEE.